Universities as Sites of Class Conflict - Nicholas Cummins (The Political Librarian, 2025)
Universities are sites of class conflict, and in this era of renewed reactionary repression and uncoordinated institutional responses, academics generally – and librarians specifically – can leverage this confusion to advocate for material change. Although right-wing critiques of higher education contain elements of truth, their analysis lacks legitimacy because it relies primarily on cultural grievances, not class conflict. Instead, a class-based critique of universities as elite institutions and enforcers of the status quo allows for socialists and their allies to properly diagnose the ills of capitalism’s capture of higher education. Some potential tools and methods to enact change are then provided.
Keywords: capitalism; universities; neoliberalism; class conflict; academy; Department of Defense; Israel; lethal autonomous weapons (LAWs); Artificial Intelligence (AI); librarians